Study of Power Relations in The Practice of Obedience of Islamic Religious Teaching at SD Muhammadiyah Malang Raya - Mohammad Kamaludin; Bagong Suyanto; Siti Mas'udah (PT. EQUATOR SINAR AKADEMIA, 2023)
This research is an attempt to see the other side of Islamic religious education. Previously, research was always emphasized on examining patterns, systems, or a series of learning and teaching mechanisms in an orderly and steady form. Therefore, a system of discipline and obedience is needed for students who are targeted as objects of that order. The other side of this research lies in an in-depth examination of compliance, not only aiming from a psychological perspective but at revealing the hidden meanings behind the actors who want the obedience attitude of students to occur. The goal is clear to photograph the obedience behavior of students based on the concepts that already exist in the agreed pattern and system of religious education. This study uses a qualitative approach by analyzing critically the teacher's understandings that have occurred so far. In the initial observations, it is not clear how the question of student compliance is sociologically constructed, although it is widely known that the question of compliance is the psychological formation of students for the sake of ease of learning. In the end, the researcher found out that not all compliance was interpreted the same by everyone. They will interpret obedience according to the context of the times. There are those who say that obedience is not always subject to submission, there are those who assume that obedience can be understood from only one side, namely those who govern and so on.